(untitled) (GAIMS Journal of Medical Sciences, 2026)
Background: Intrauterine fetal death (IUFD) is a tragic outcome with emotional and clinical consequences, reflecting the quality of antenatal care. Material and methods: A prospective observational study was conducted at C.U. Shah Medical College and Hospital, Gujarat, from May 2023 to May 2024. Out of 1923 total deliveries, 100 IUFD cases at ≥28 weeks gestation was analyzed for clinical presentation, risk factors, and outcomes. Results: IUFD incidence was 3.73%. Most patients were aged 21–25 years and multiparous. Common symptoms included abdominal pain and decreased fetal movement. Major risk factors were pregnancy-induced hypertension, antepartum hemorrhage, and anemia. The majority delivered vaginally, with 23% undergoing cesarean section. Macerated stillbirths were more frequent, suggesting delayed recognition. Postpartum complications such as coagulopathy and breast issues were noted. Contraceptive acceptance postpartum remained low. Conclusion: IUFD continues to be a major concern in maternal health. Early detection of high-risk pregnancies, consistent antenatal care, and postpartum counseling are essential to reduce its incidence and improve outcomes.